The place of the humanities in today’s knowledge society - Costa, R. C. (Palgrave Communications, 2019)
Over the past four decades, the humanities have been subject to a progressive devaluation within the academic world, with early instances of this phenomenon tracing back to the USA and the UK. There are several clues as to how the university has generally been placing a lower importance on these fields, such as through the elimination of courses or even whole departments. It is worth mentioning that this discrimination against humanities degrees is indirect in nature, as it is in fact mostly the result of the systematic promotion of other fields, particularly, for instance, business management. Such a phenomenon has nonetheless resulted in a considerable reduction in the percentage of humanities graduates within a set of 30 OECD countries, when compared to other areas. In some countries, a decline can even be observed in relation to their absolute numbers, especially with regards to doctorate degrees. This article sheds some light on examples of international political guidelines, laid out by the OECD and the World Bank, which have contributed to this devaluation. It takes a look at the impacts of shrinking resources within academic departments of the humanities, both inside and outside of the university, while assessing the benefits and value of studying these fields. A case is made that a society that is assumed to be ideally based on knowledge should be more permeable and welcoming to the different and unique disciplines that produce it, placing fair and impartial value on its respective fields.